Messplatzgestützte multimediale Analyse wesentlicher Leistungsparameter mittels der neuen Software MotionTuner Online am Beispiel der olympischen Kanusportarten - Klein, O.-M.; Schmidt, K.-H.; Kratt, D.; Käding, C.; Siebert, D. (Leipziger Sportwissenschaftliche Beiträge, 2017)
In this article the web application MotionTuner Online is presented as a tool for the sports scientist, trainer and athlete. The program introduces innovative possibilities to present and compare essential biomechanical, conditional and technical-tactical parameters of performances in competition and training. Developed for Olympic canoeing, it unifies various features and visualizations, which are also used in other sports. The combined and synchronized representation of the motoric performance is particularly important. Thus the software reveals integrative possibilities for performance analysis and supports meeting the demand for a holistic performance diagnosis. The web browserbased software is independent of location and operating system and offers a wide range of options for utilization. For this reason, it is suitable both as an instrument of process-accompanying performance analysis and as a research tool for processing further scientific questions.